2010
DOI: 10.1159/000321114
|View full text |Cite
|
Sign up to set email alerts
|

Th2-Biased Immune Responses Are Important in a Murine Model of Chronic Hypersensitivity Pneumonitis

Abstract: Background: Chronic hypersensitivity pneumonitis (HP) can lead to irreversible pulmonary fibrosis. A good animal model is essential to elucidate the mechanisms of this disease. We previously reported that a Th2 predominance may play an important role in the fibrogenesis in chronic HP patients. A study was undertaken to evaluate whether Th2-biased immune responses were crucial during the processes of lung fibrosis in a murine model of chronic HP. Methods: Instillation of pigeon dropping extracts (PDE) was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 69 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…A study on farmer's lung, another type of HP, revealed that large numbers of lymphocytes and high levels of IL-2 are present in the bronchoalveolar lavage fluid of people exposed to allergens, which might result in lymphocyte accumulation in the lung. Moreover, serum soluble IL-2 receptor was found to be expressed at a high level [17], and PF and Th2 dominance were observed when the disease evolved to the chronic stage; IL-4 was also produced by Th2 cells at a higher level [8]. In our previous study, Th1-associated cytokines were found to be highly expressed in PBL patients.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 79%
See 1 more Smart Citation
“…A study on farmer's lung, another type of HP, revealed that large numbers of lymphocytes and high levels of IL-2 are present in the bronchoalveolar lavage fluid of people exposed to allergens, which might result in lymphocyte accumulation in the lung. Moreover, serum soluble IL-2 receptor was found to be expressed at a high level [17], and PF and Th2 dominance were observed when the disease evolved to the chronic stage; IL-4 was also produced by Th2 cells at a higher level [8]. In our previous study, Th1-associated cytokines were found to be highly expressed in PBL patients.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 79%
“…According to a clinical study on HP, the expression levels of proinflammatory factors, such as IL-2 and IFN-γ, in bronchoalveolar lavage fluid and TNF-α in serum are markedly increased [4,7]. However, according to an animal study, Th2 cell dominance and PF occur together in chronic stages, and IL-4 is highly expressed [8].…”
Section: Xiaohong Yangmentioning
confidence: 99%
“…A study which looked at T cell responses in patients with subacute and chronic pigeon breeder's disease, another common type of HP, found an increase in CD4 + and CD8 + T cells expressing IL-4 and a decrease in T cells expressing IFNγ in patients with CHP compared to subacute HP (Barrera et al, 2008). This is in agreement with a mouse model of chronic pigeon breeder's disease in which the authors found that IL-4 / IL-13 expression and a Th2-biased immune response correlated with increased lung fibrosis (Mitaka et al, 2011). Fibrotic diseases are often associated with the expression of Th2-associated cytokines IL-4 and IL-13 (GharaeeKermani et al, 2001;Huaux et al, 2003;Jakubzick et al, 2003;Lee et al, 2001).…”
Section: Chapter 5 Chronic Phase Introductionsupporting
confidence: 78%
“…lung fibrosis in the Th2-biased mouse strain A/J (Mitaka et al, 2011). However, in the SR model of HP, IL-17 and a Th17 response is associated with increased fibrosis (Joshi et al, 2009;Simonian et al, 2009).…”
Section: Mice With Long Term Exposure To Sr Have Increased Expressionmentioning
confidence: 97%
“…These patients were diagnosed with pigeon breeders disease, another type of HP in which the chronic phase is characterized by fibrosis. Similarly, Mitaka et al (28) used the murine model of pigeon breeders disease to demonstrate an association between fibrosis and the Th2 response. However, patients with chronic FLD develop both emphysematous and fibrotic changes in the lung, suggesting that the immunological mechanisms leading to lung damage in HP may differ depending on the environmental antigen triggering the disease (12).…”
mentioning
confidence: 99%